At the Crossroad of Literary Links - TER-GRIGORYAN, RUZAN (Bulletin of Yerevan University H: Russian Philology, 2021)
The monthly magazine “Bazmavep”, issued from 1843 by Congregation of Mchitarist’s (Venice, St.Lazar Island) has occupied a peculiar place in the history of Armenian-Russian literary links. I.Krilov, I.Dmitriev, G.Derzhavin, A.Pushkin, M.Lermontov,N.Nekrasov, N.Gogol, I.Turgenev, L.Tolstoy, A.Chekhov, M.Gorki, L.Andreev: all these and other names appeared on the pages of “Bazmavep”. Different materials connected with these authors have been published in the magazine: biographical data, essays, literary criticism, translations of certain works, articles on Russian history and culture.
Keywords: Kongregation of mchitarists, Venice, , Russian literature, translation